Analisa Wacana Kritis pada Peraturan Menteri Nomor 30 Tahun 2021 Tentang Pencegahan Kekerasan Seksual - Wulan Yulian Anggini (LITERATUS, 2022)
Indonesian education so far has kept a problem that has not received the attention of all stakeholders, namely sexual violence that occurs to students. Victims are faced with the power relations of educational institutions whose reputation is tarnished because of cases of sexual violence. The existence of social media as a social driver is able to mobilize cases of sexual violence on Campus to become a national issue. This prompted the Ministry of Education and Culture to issue Ministerial Regulation no. 30 of 2021 concerning the prevention and handling of sexual violence in universities. This research focuses on critical discourse analysis of this Ministerial Regulation. This research is a descriptive-qualitative research type. To gain comprehensive power of qualitative research analysis, the research phase requires the power of reason which is the source of analytical ability (Arikunto, 2010). The scalpel uses the critical discourse analysis technique of Norman Fairclough's model. The main study is focused on microstructural (text), mesostructure (discourse practices), and macrostructural (sociocultural practices) data. The study results are, first, this regulation is motivated by the phenomenon of the iceberg of sexual violence in the university environment. The government feels the need to provide legal certainty to perpetrators and victims. Second, in this regulation, the government uses educational narratives, prevention, and handling, protecting whistleblowers, and restoring victims' rights. Third, this regulation impacts the social life of the community through various responses.